Air pollution and female fertility: a systematic review of literature - Alessandro Conforti; Marika Mascia; Giuseppina Cioffi; Cristina De Angelis; Giuseppe Coppola; Pasquale De Rosa; Rosario Pivonello; Carlo Alviggi; Giuseppe De Placido (BMC, 2018)
Abstract Air pollution is a cause of concern for human health. For instance, it is associated with an increased risk for cancer, cardiovascular and respiratory disorders. In vitro and in vivo studies suggested that air pollutants could act as endocrine disruptors, promote oxidative stress and exert genotoxic effect. Whether air pollution affects female infertility is under debate. The aim of the present study was to conduct a systematic review of studies that evaluated the impact of air pollution on female infertility. We systematically searched the MEDLINE (PubMed) and SCOPUS databases to identify all relevant studies published before October 2017. No time or language restrictions were adopted, and queries were limited to human studies. We also hand-searched the reference lists of relevant studies to ensure we did not miss pertinent studies. The risk of bias and quality assessment of the studies identified were performed using the Newcastle-Ottawa Scale. Primary outcomes were conception rate after spontaneous intercourse and live birth rate after in vitro fertilization (IVF) procedures. Secondary outcomes were first trimester miscarriage, stillbirths, infertility, number of oocytes and embryo retrieved. Eleven articles were included in the analysis. We found that in the IVF population, nitrogen dioxide and ozone were associated with a reduced live birth rate while particulate matter of 10 mm was associated with increased miscarriage. Furthermore, in the general population, particulate matter of 2.5 mm and between 2.5 and 10 mm were associated with reduced fecundability, whereas sulfur dioxide, carbon monoxide and nitrogen dioxide might promote miscarriage and stillbirths. The main limitation of our findigns resides in the fact that the desegn of studies included are observational and retrospective. Furthermore, there was a wide heterogenity among studies. Although larger trials are required before drawing definitive conclusions, it seems that air pollution could represent a matter of concern for female infertility.